Hubungan antara Infeksi Cacing dan Alergi - Yolazenia Yolazenia; Taniawati Supali; Heri Wibowo (Jurnal Ilmu Kedokteran, 2010)
Many researches showing the evidence of a reverse relation between helminthiasis and allergic diseases in tropicaldeveloping countries, supported by hygiene hypothesis. There is relationship between the inflammation caused byallergic and helminthiasis. Both, allergic and helminthiasis, show the increase of IgE level, eosinophilia, mastocytosis,and release of IL-4, IL-5 and IL-13 cytokines by Th2. Several mechanisms explaining the decrease of allergicmanifestation in people with helminthiasis are polyclonal IgE blocking, suppression of anti-inflammatory cytokines(IL-10 and TGF-â), and IgG4 blocking antibody.